PROPHYLACTIC EFFECTIVENESS OF FUSAFUNGINE IN CHILDREN WITH CHRONIC TONSILLITIS - T.I. Garashchenko; M.V. Garashchenko; I.A. Kubylinskaya; N.V. Ovechkina; T.G. Kats ("Paediatrician" Publishers LLC, 2010)
In 2008/2009, at the time of influenza epidemic, the study of ambulatory prophylactic treatment of fusafungine (Bioparox) in 50 children 7-15 years old with chronic tonsillitis was performed. All these children underwent regular ENT check-up. The control group included 50 schoolchildren the same age without chronic diseases of upper airways. After the treatment with intranasal fusafungine, the amount of patients with Streptococcus pyogenes was decreased 1,6 times low (and after 3 months of treatment it was decreased 3,5 times low). The sanation of palatine tonsils from Candida albicans was detected (eradication of microorganism was achieved in 58% of cases, and the amount of patients with pharyngomycosis was decreased 2,4 times low). Patient's quality of life significantly increased, and ENT-specialists met less complaints (in 4,5-15 times low). The morbidity with respiratory infections in 3 months after the treatment with fusafungine was 7,5 times low than in control group.Key words: schoolchildren, chronic tonsillitis, acute respiratory infection, fusafungine.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):26-31)